Urinary exosomes reveal protein signatures in hypertensive patients with albuminuria - Gonzalez-Calero, Laura (Oncotarget, 2017)
Albuminuria is an indicator of cardiovascular risk and renal damage in hypertensive individuals. Chronic renin–angiotensin system (RAS) suppression facilitates blood pressure control and prevents development of new-onset-albuminuria. A significant number of patients, however, develop albuminuria despite chronic RAS blockade, and the physiopathological mechanisms are underexplored. Urinary exosomes reflect pathological changes taking place in the kidney. The objective of this work was to examine exosomal protein alterations in hypertensive patients with albuminuria in the presence of chronic RAS suppression, to find novel clues underlying its development. Patients were followed-up for three years and were classified as: a) patients with persistent normoalbuminuria; b) patients developing de novo albuminuria; and c) patients with maintained albuminuria. Exosomal protein alterations between groups were identified by isobaric tag quantitation (iTRAQ). Confirmation was approached by target analysis (SRM). In total, 487 proteins were identified with high confidence. Specifically, 48 proteins showed an altered pattern in response to hypertension and/or albuminuria. Out of them, 21 proteins interact together in three main functional clusters: glycosaminoglycan degradation, coagulation and complement system, and oxidative stress. The identified proteins constitute potential targets for drug development and may help to define therapeutic strategies to evade albuminuria progression in hypertensive patients chronically treated.